Utero-vaginal prolapse: A community study at Duradada, Lamjung, Nepal - Adhikari, Prabhat (Nepal Journal of Obstetrics and Gynaecology, 2014)
DOI: http://dx.doi.org/10.3126/njog.v3i2.10838 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 66